Particle-Based Modeling of Asymmetric Flexible Fibers in Viscous Flows (Communications in Computational Physics, 2017)
The present paper follows our previous work [Yang et al., Phys. Rev. E,90 (2014), 063011] in which the bending modes of a symmetric flexible fiber in viscousflows were studied by using a coupling approach of smoothed particle hydrodynamics(SPH) and element bending group (EBG). It was shown that a symmetric flexible fibercan undergo four different bending modes including stable U-shape, slight swing, violentflapping and stable closure modes. For an asymmetric flexible fiber, the bendingmodes can be different. This paper numerically studies the fiber shape, flow field andfluid drag of an asymmetric flexible fiber immersed in a viscous fluid flow by using theSPH-EBG coupling method. An asymmetric number is defined to describe the asymmetryof a flexible fiber. The effects of the asymmetric number on the fiber shape, flowfield and fluid drag are investigated.